Molecular and palaeoecological evidence for multiple glacial refugia for evergreen oaks on the Iberian Peninsula - López de Heredia, U.; Carrión, J. S.; JIMÉNEZ, P.; COLLADA, C.; Gil, L. (Journal of Biogeography, 2007)
Aim A multiple glacial refugia hypothesis for Mediterranean plant species was tested with the evergreen Quercus complex (Quercus suber L., Quercus ilex L. and Quercus coccifera L.) from the Iberian Peninsula, using molecular and palaeobotanical data. Location The Iberian Peninsula, which is an ecologically and physiographically complex area located on the western edge of the Mediterranean Basin. Methods We sampled 1522 individuals from 164 populations of Q. suber, Q. ilex and Q. coccifera. A review of the recent literature on fossil pollen and charcoal records and a nested clade analysis on chloroplast DNA polymerase chain reaction-restriction fragment length polymorphism was carried out to infer demographic and historical processes. Results The analysis indicates at least one glacial refugium for Q. suber in southwestern Iberia. Extensive introgression of Q. suber with Q. ilex indicates several potential refugia in eastern Iberia. Past fragmentation was followed by a restricted range ﬂow/range expansion, suggesting multiple refugia for Q. ilex–Q. coccifera elsewhere in central and northern Iberia and multiple areas of secondary contact. This ﬁnding is consistent with fossil records. Main conclusions The predicted multiple refugia during glacial periods indicates the existence of secondary post-glaciation contact areas. These areas contained complex diversity patterns resulting mainly from range expansions followed by isolation by distance. To a lesser degree, traces of restricted and longdistance dispersal were also found.
Keywords: cpDNA PCR-RFLPs; evergreen Quercus; fossil pollen; glacial refugia; iberian peninsula; introgression; nested clade analysis; oaks; phylogeography

Análisis de la variabilidad de adn de cloroplastos en Quercus ilex L., Q. suber L. Y Q. coccifera L.. - COLLADA, C.; JIMÉNEZ, P.; Gil, L. (III Congreso Forestal Español, 2001)
Chloroplast (Cp) and mitochondrial (mt) DNA variation have been studied by PCR-RFLP in 14 location (13 with Q. suber, 12 with Q. ilex and 6 with Q. coccifera) along the natural distribution area of these species in the Iberian Peninsula. Five chloroplast DNA primers pairs and one mitochondrial DNA primer pair have been used, each one in combination with a restriction enzyme. 29 different haplotypes have been detected, In the case of Q. suber a characteristic haplotype, very divergent of the remaining ones has been described. Usually, species don’t share haplotypes within the same populations. The distribution of haplotypes suggests a geographical structuring. The levels of genetic differentiation are similar to those obtained in oaks.hS is significantly higher in Q. ilex (hS=0,262). Differentiation coefficients (Gst) are similar in the three species and indicate a high typical structuring of maternal markers.
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español pub-location: Granada
Keywords: chloroplast DNA; differentiation; geographic distribution; Haplotypes; phylogeny; Quercus